Charisma in Christian Tradition - Lemwang Chuhwanglim (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2019)
The term charisma had been used and continues to use by many people in different context. There is charisma in social, political, sports, culture and other modern leadership who have made many great impacts in winning people’s minds and hearts. This paper aims to analyze the meaning of Charisma in the Christian tradition and how it influences in society until today. In doing so the article aims to see both negative and positive aspects and influence of charisma in different Christian social context. Though the article may not give an absolute picture of the Christian tradition charisma being understood among other Christian denominations, it gives people to revisit the origin of the term Charisma and its evolution in the New Testament by the Apostle Paul. Hence, this article will analyze the meaning of Charisma in the Christian tradition and how it influences in Christian society until today and the authority of God being interpreted by charismatic group within and outside the Church.Keywords: Charisma, Holy Spirit, Grace